EFEKTIVITAS PEMBELAJARAN EXTRA TIME BERBASIS TEKNOLOGI DALAM MATA PELAJARAN IPA - Martono, Stefany Margareta; Suryani, Luluk; VAN HARLING, VINA N (SOSCIED, 2025)
This study aims to examine the effectiveness of technology-assisted extra time learning in science subjects. The approach used in this research is qualitative. The research design is descriptive, in which the researcher describes the implementation of the technology- assisted extra time learning and the students responses during the learning process. Data were collected through non-participant observation, open-ended questionnaires, and summative assessment scores. The result show that students who participated in the technology-assisted extra time learning experienced a significant improvement in their science learning outcomes, with an increase of 75,2%. The average score from non-participant observations was 82,66. This indicates that students were able to utilize the additional time effectively, make use of technology, complete exercise, create independent study schedules, and demonstrate discipline during the implementation of this learning method. Furthermore, data from the open-ended questionnaires revealed that students were more enthusiastic and better understood the material through learning videos, and the implementation of extra time greatly supported them in completing summative assessments.